Analysis on the piezotronic effect in a strained piezo-Schottky junction with AC impedance spectroscopy. (June 2017) - Li, Yunxia; Zhang, Zeming; Han, Weihua; Jiang, Changjun; Xie, Erqing
Abstract: Piezotronic effect is always mixed with piezoresistive effect when we investigate the electronic transport behaviors in the study of piezotronic devices. It is essential to separate the two effects, which is beneficial to the data analysis in actual applications. Here, we report a general method, alternative current (AC) impedance spectroscopy, to distinguish the piezotronic and piezoresistive effects in a strained piezo-Schottky junction. The study was performed on a copper (Cu) layer and F:SnO2 ( FTO) glass sandwiched zinc oxide (ZnO) nanowire arrays (Cu/ZnO/FTO). The AC spectra measured at various stress were simulated with appropriate equivalent circuits to reveal the possible change in the device. Our results showed the dominant role of piezotronic effect in the Cu/ZnO/FTO structure instead of piezoresistive effect which has been suspected previously. A capacitive effect of the sputtered ZnO seed layer was also observed. The origin of the capacitance was verified by the bias-independent impedance diagrams. This technique has provided a powerful tool to quantitative analysis on the inner changes of a strained piezotronic device, not only piezo-Schottky junction-based diodes, but also pn junction-based phototronics. Graphical abstract: Alternative current (AC) impedance spectroscopy has been used to estimate the inner changes in a strained piezo-Schottky junction. Highlights: A piezo-Schottky junction was fabricated with vertically-aligned ZnO nanowire arrays. Piezotronic effect was investigated with AC impedance spectroscopy. A capacitance effect from the seed layer was observed and investigated. A powerful tool was proposed to distinguish the inner changes of piezotronic devices.